2013
DOI: 10.1021/ja408430v
|View full text |Cite
|
Sign up to set email alerts
|

Single-Handed Helical Wrapping of Single-Walled Carbon Nanotubes by Chiral, Ionic, Semiconducting Polymers

Abstract: We establish the requisite design for aryleneethynylene polymers that give rise to single-handed helical wrapping of single-walled carbon nanotubes (SWNTs). Highly charged semiconducting polymers that utilize either an (R)- or (S)-1,1'-bi-2-naphthol component in their respective conjugated backbones manifest HRTEM and AFM images of single-chain-wrapped SWNTs that reveal significant preferences for the anticipated helical wrapping handedness; statistical analysis of these images, however, indicates that ∼20% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 99 publications
2
80
2
Order By: Relevance
“…In the past decade, there are several reports regarding helical wrapping of single polymers around CNTs. [14] However, because of the size limitation of polymer chains, those helical surface nanostructures are not as obvious as those reported in our present work. The helical wrapping of single polymers is found to enhance properties of or give additional functionality to composites.…”
Section: Introductioncontrasting
confidence: 73%
“…In the past decade, there are several reports regarding helical wrapping of single polymers around CNTs. [14] However, because of the size limitation of polymer chains, those helical surface nanostructures are not as obvious as those reported in our present work. The helical wrapping of single polymers is found to enhance properties of or give additional functionality to composites.…”
Section: Introductioncontrasting
confidence: 73%
“…[83,151] Similar approaches have been used to flocculate graphene/ethyl cellulose following exfoliation. [163,164] Following sorting, it is necessary to strip the poorly conductive conjugated polymers from the tube walls to improve the charge transport, but their strong affinity for SWCNTs defies effective removal through rinsing at low temperatures. Polyfluorene and polythiophene derivatives or copolymers have been heavily investigated to target specific chiralities of SWCNTs.…”
Section: Separation Methods For Improving Nanomaterials Monodispersitymentioning
confidence: 99%
“…[157,161] In addition, single-handedness SWCNT enantiomers have been separated using conjugated polymers with chiral moieties. [163,164] Following sorting, it is necessary to strip the poorly conductive conjugated polymers from the tube walls to improve the charge transport, but their strong affinity for SWCNTs defies effective removal through rinsing at low temperatures. [165] One method for releasing these polymers is to trigger their conformation change by acids [166] or chelating agents.…”
Section: Separation Methods For Improving Nanomaterials Monodispersitymentioning
confidence: 99%
“…have been studied in order to obtain near-monochiral suspensions through polymer wrapping. [122][123][124][125] Moreover, recent results demonstrated that this technique allows discrimination between right-and left-handed SWNTs. 126,127 Nakashima and co-workers designed copolymers composed of polyfluorene Reproduced with permission of the American Chemical Society from ref.…”
Section: Nanoscale Accepted Manuscriptmentioning
confidence: 99%